Experimental and nonlinear finite element analysis for post-tensioned precast frames with mechanical joints - Won-Kee Hong; Tien Dat Pham; Dinh Han Nguyen; Thuc Anh Le; Manh Cuong Nguyen; Van Tien Nguyen (Journal of Asian Architecture and Building Engineering)
Conventional cast-in-place frames using a pair of steel plates are replaced by a post-tensioned H-shaped precast frame with mechanical joints in which plates are used to transfer loads between them. The mechanical joints strengthened by interior bolts are used, providing a flexural capacity of columns to a level similar to that of conventional monolithic connections. In the present study, strain evolutions of the proposed frames are explored using a finite element analysis with a concrete plasticity model (CP) applying a 0% damage index representing undamaged concrete for the first floor and a concrete damaged plasticity model (CDP) model implementing 80% damage index for the second floor when using ABAQUS. FEA-based strain evolutions are, then, verified by experimental results obtained from full-scale tests, showing agreements except for places where gauges malfunctioned. This study identifies structural behaviors and contributions of each structural element of the mechanical joint to flexural capacity. Microscopic strain evolutions of the post-tensioned H-shaped precast frames with mechanical joints agreed with the test data. Both experimental and numerical investigations demonstrate the structural performance of the proposed prestressed frames with mechanical joints is predictable and stable under service loads.